PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN PUBLIK TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2018 - Purba, Imelda (Jurnal Riset Akuntansi & Keuangan, 2021)
The purpose of this study is to obtain empirical evidence of the influence of managerial ownership, institutional ownership and public ownership on firm value in property and real estate companies in the 2016-2018 period. This type of research is quantitative research. The data used in this research is secondary data. The population in this study includes all property and real estate companies listed on the IDX in the 2016-2018 period. The sample in this study were 16 companies that met the criteria. The sampling technique in this study using purposive sampling. The data analysis used to test the hypothesis is multiple regression with a significance level of 5% and by using the SPSS version 23 tool. The results of this study indicate that managerial ownership variables have no effect on firm value, while institutional ownership and public ownership have a partial effect on firm value. Managerial ownership, institutional ownership, and public ownership have a simultaneous effect on firm value.